2011
DOI: 10.1177/1359104510396432
|View full text |Cite
|
Sign up to set email alerts
|

Attention-deficit hyperactivity disorder, drug companies and the internet

Abstract: This study investigated the influence of drug-company funding on websites about attention-deficit hyperactivity disorder (ADHD). Websites in the top 60 for either Google or Yahoo!Xtra with information about causation and treatment were analysed. Likert scales, based on those used in previous similar studies, were developed to rate aetiological explanations and recommended treatment approaches, on a dimension from psycho-social to biological. Overall, the quality of information on websites was poor with a stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 74 publications
(95 reference statements)
2
38
1
Order By: Relevance
“…All of the Web sites were easy to navigate and understand for a first time user. This finding was largely inconsistent with the Web site research undertaken by Mitchell and Read (2012), who found that information on many Web sites was written in highly technical language. Fewer than 33% of the Web sites evaluated disclosed authorship of the information displayed, and fewer than half of those displayed both authorship and the author's actual qualifications.…”
contrasting
confidence: 69%
See 1 more Smart Citation
“…All of the Web sites were easy to navigate and understand for a first time user. This finding was largely inconsistent with the Web site research undertaken by Mitchell and Read (2012), who found that information on many Web sites was written in highly technical language. Fewer than 33% of the Web sites evaluated disclosed authorship of the information displayed, and fewer than half of those displayed both authorship and the author's actual qualifications.…”
contrasting
confidence: 69%
“…Web sites devoted to modern health issues have become the public's main source of information (Mitchell and Read 2012). Anderson and Klemm (2008) suggest that the Internet has changed how patients with chronic illness, especially cancer patients, learn about their disease and how to cope with it.…”
Section: Internet-based Healthmentioning
confidence: 99%
“…(Erlandsson et al, 2016; (Freedman, 2015; Mitchell & Read, 2012). This may have contributed to the rising use of medication over the years.…”
Section: Medication Does Not Benefit Most Children In the Long Runmentioning
confidence: 99%
“…In this review, we focus on the sympathomimetic actions of MPH currently the most widely used ADHD drug [102,103] within a quite dynamic market [103]-on cardiovascular function, which represent an issue of concern [104]. However, because the sympathomimetic action of MPH is similar to that of both amphetamine salts and atomoxetine, the same concerns pertaining to long-term cardiovascular safety also apply to these medications.…”
Section: Pharmacological Data and Potential Consequencesmentioning
confidence: 98%